Understanding the non-institutionalization of a socio-technical innovation: the case of multiple-use water services (MUS) in Nepal. Issue 4 (19th May 2019) - Clement, Floriane; Pradhan, Prachanda; Van Koppen, Barbara
ABSTRACT: Multiple-use water services (MUS) have been promoted and piloted globally for two decades as a socio-technical innovation. Yet the MUS approach has hardly extended beyond donor-funded projects to public policies. We use a collective action framework to analyze the non-institutionalization of MUS in Nepal. We find that MUS has much cognitive legitimacy, but discourse fragmentation has reduced its socio-political legitimacy. Yet the latter is essential to overcome the institutional challenges of a fragmented public water sector and to mainstream MUS into policy debate.